2020
DOI: 10.18502/jchr.v9i4.4975
|View full text |Cite
|
Sign up to set email alerts
|

Health Information-Seeking Behavior of Iranian first-time Mothers and First-Time Pregnant Women in Northwest Health Centers of Tehran

Abstract: Introduction: Pregnancy, especially the first pregnancy and childbirth, affects the women’s quality of life. Improving information-seeking behavior facilitates the decision-making process of women during pregnancy and postpartum. The aim of this study was to investigate the health information-seeking behavior of Iranian first-time mothers and first-time pregnant women. Methods: This research was a cross-sectional-descriptive survey .A self-administered questionnaire was distributed among 358 first-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Doctors should encourage pregnant women to maintain a balanced diet and take supplements in the case of deficiencies. In an Iranian study, scientists indicated that the main source of information commonly used by patients was a gynecologist [16]. It has been shown that providing appropriate health education among pregnant women is an important aspect of prenatal care [17].…”
Section: Discussionmentioning
confidence: 99%
“…Doctors should encourage pregnant women to maintain a balanced diet and take supplements in the case of deficiencies. In an Iranian study, scientists indicated that the main source of information commonly used by patients was a gynecologist [16]. It has been shown that providing appropriate health education among pregnant women is an important aspect of prenatal care [17].…”
Section: Discussionmentioning
confidence: 99%
“…12 Making such information readily available may increase the health literacy of mothers. 13 Sharing information during pregnancy with peers and healthcare professionals promotes the decision-making process of pregnant women on prenatal care, postnatal care, and newborn care, and it would facilitate their ability to manage their pregnancy well. 5 Pregnant women use different sources of information to obtain information.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Health information-seeking for various health-related reasons is common during pregnancy. 1822 A recent systematic review reported that formal sources (e.g. health care providers), informal sources (e.g.…”
Section: Introductionmentioning
confidence: 99%